Factors associated with safe medication administration in specified residential facilities for older persons within the Metro-North, Western Cape Province - Nicholson, Emerentia Cynthia (Stellenbosch : Stellenbosch University, 2021)
Thesis (MNur)--Stellenbosch University, 2021.